Constructions of older people's identities in Indonesian regional ageing policies: the impacts on micro and macro experiences of ageing. Issue 9 (7th September 2022) - Lestari, Made Diah; Stephens, Christine; Morison, Tracy
Abstract: As Indonesia experiences rapid growth of the ageing population, the government's attention has turned to the wellbeing of older people. This study aims to review critically the construction of older people's identity and care within regional ageing policies in Indonesia. Working from a critical gerontology perspective, a critical discourse analysis of 16 regional ageing policies identified two constructions, labelled 'material' and 'cultural' ageing, which were used to position older people. The analysis showed that 'material ageing' positions older people at the intersection of 'decline' and 'successful ageing' discourses, while 'cultural ageing' positions older people's welfare at the intersection of 'public responsibility' and 'family obligation' discourses. These discursive constructions in the policy documents have both micro (interpersonal) and macro (structural) constructive effects. At the micro-level, the regional ageing policies stand at a crossroad between empowering and marginalising older people and their families. While the dominant discourse of 'successful ageing' encourages older people to be healthy, it marginalises those who do not, or cannot, meet its criteria, undermining a rehabilitative approach as a policy priority. In addition, the rights of the family are overlooked, despite being a pivotal element of cultural ageing. At the macro level, a moral dilemma appears in defining the public and private domains of older people's welfare. Eligibility requirements for state assistance (due to budgetary constraints) ensure that elder care is often relegated to the private sphere, without support. Recommendations for policy improvement are discussed, including the recognition of families' rights and the importance of local cultural practices in providing care for older people.